PENGAWASAN UPAH MINIMUM BERDASARKAN UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH (Studi Implementasi Pada Mal Kota Kasablanka Jakarta Selatan) - Ersa Hamzah (2022)
The division of concurrent government affairs is the ideal of the 1945 Constitution of the Republic of Indonesia, in which the implementation of autonomy for the wider region is aimed at managing their own household. Concurrent government affairs cover many fields, one of which is employment. Manpower affairs are divided into two chambers between the Central Government and the Provincial Government. In supervising the provision of this minimum wage, it is the provincial government that is responsible for administering it in accordance with the mandate of Law Number 23 of 2014 concerning Regional Government. Supervision of the provision of minimum wages is intended to provide legal certainty for workers to earn a decent living. The purpose of this paper is to provide an explanation in terms of how the division of concurrent government affairs in supervising the provision of the DKI Jakarta minimum wage and the implementation of supervision that has been carried out by the Provincial Government. The research method that will be used is empirical juridical research using primary data through interviews (Field Study) and secondary data from a statutory approach (Statute Approach). The results of this study explain that the division of affairs is not synchronized and the supervision of the minimum wage has not been maximized in creating justice for workers.